Empowerment of Tourism With Eco-Green Concept-Based Ecotourism in Botubarani Village - Podungge, Abdul Wahab; Hunawa, Robby; Alisa, Alisa; Sipahutar, Christy Anastasya (DAS SEIN: Jurnal Pengabdian Hukum dan Humaniora (Journal of Legal Services and Humanities), 2022)
This research aims to provide knowledge and skills to the people of Botubarani Village with an approach to solve local problems with problem-solving techniques through design thinking. The output targets of this program include the opportunity for independent study program students certified as independent campuses to analyze problems that exist in the community related to ecotourism. The implementation method in this activity is Focus Group Discussion (FGD) between field supervisors and students with partner groups and the community. Conduct direct observations together with partners and document the potential that will be developed with the assisted communities in Botubarani Village. Designing program implementation scenarios, conducting training and mentoring for the utilization of waste.Ecotourism problems in the village of Botubarani were discussed by a team of writers using the Customer validation technique. The results of interviews with tourists and customers will then provide an overview of the solutions that must be carried out by our team later through product validation techniques. Products that have been validated will then be realized through a prototyping procedure which will later be distributed to residents in the form of training and also enrichment of concepts through open discussions. Because this project is based on human centricity, all solutions and problems are obtained through observation and user validation. With these procedures and techniques, we are expected to be able to provide the best solutions for validated problems to realize sustainable and sustainable ecotourism with an eco-green concept.